2013
DOI: 10.1080/0972060x.2013.764180
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Effect of Sage and Turkish Oregano Volatile Oils onIn Vitroin Sainfoin (Onobrychis viciifolia)

Abstract: Sainfoin has little atention for plant tissue culture studies. However, genetic engineering applications of gene transfer can be done today. Therefore, first different methods are used in tissue culture (For example, using of different hormones for plant growing) and be given importance. In this study, the effect of different concentration (0-5-10-20-30 ppm) sage (Salvia officinalis L.) and Turkish oregano (Origanum onites L.) have profound effects on morphology of the tissues that grow from the initial sainfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Origanum species have a rich biological activity such as antibacterial, antifungal, antioxidant, anti-inflammatory, antitumor, antiviral and antiparasitic activities (García-Beltrán and Esteban 2015). Also, it has been reported that Origanum onites essential oil has allelopathic activity on the seed germination, plant height, root length and root number of Onobrychis viciifolia under in vitro conditions (Altindal and Altindal 2013). O. onites essential oil has had a high inhibiting effect on the seed germinations of A. retroflexus, Centaurea solstitialis, Sinapis arvensis, Sonchus oleraceus, Raphanus raphanistrum and Rumex nepalensis (Azirak and Karaman 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Origanum species have a rich biological activity such as antibacterial, antifungal, antioxidant, anti-inflammatory, antitumor, antiviral and antiparasitic activities (García-Beltrán and Esteban 2015). Also, it has been reported that Origanum onites essential oil has allelopathic activity on the seed germination, plant height, root length and root number of Onobrychis viciifolia under in vitro conditions (Altindal and Altindal 2013). O. onites essential oil has had a high inhibiting effect on the seed germinations of A. retroflexus, Centaurea solstitialis, Sinapis arvensis, Sonchus oleraceus, Raphanus raphanistrum and Rumex nepalensis (Azirak and Karaman 2008).…”
Section: Discussionmentioning
confidence: 99%
“…vulgare L., O. vulgare ssp. hirtum, O. acutidens , O. onites , O. compactum Benth., and O. majorana L. are the dominant species of Origanum that showed allelopathic properties [ 3 , 37 , 174 , 175 , 176 , 177 , 178 , 179 ].…”
Section: Allelopathy Of Major Lamiaceae Generamentioning
confidence: 99%